Granulomatosis with polyangiitis according to geographic origin and ethnicity: clinical-biological presentation and outcome in a French population. (7th December 2016) - Terrier, Benjamin; Dechartres, Agnès; Deligny, Christophe; Godmer, Pascal; Charles, Pierre; Hayem, Gilles; Dunogué, Bertrand; de Bandt, Michel; Cohen, Pascal; Puéchal, Xavier; Jeunne, Claire Le; Arfi, Serge; et al.
Abstract : Objectives. Granulomatosis with polyangiitis (GPA) mainly affects white Europeans, but rarely GPA may also affect non-Europeans. This study aimed to describe GPA clinical-biological presentation and outcome in black sub-Saharan Africans and Afro-Caribbeans and in North Africans. Methods. Among 914 GPA patients included in the French Vasculitis Study Group database, geographic origin and ethnicity were known for 760. Clinical-biological presentations and outcomes of white Europeans vs black sub-Saharans and Afro-Caribbeans and vs North Africans were analysed. Results. Among the 760 patients, 689 (91%) were white Europeans, 33 (4.3%) were North Africans and 22 (2.9%) were sub-Saharans (n = 8) or Afro-Caribbeans (French West Indies, n = 14). Black sub-Saharans and Afro-Caribbeans, compared with white Europeans, were significantly younger at GPA diagnosis (P = 0.003), had more frequent central nervous system involvement (P = 0.02), subglottic stenosis (P = 0.002) and pachymeningitis (P = 0.009), and tended to have more frequent chondritis and retroorbital tumour. Median serum creatinine levels and Birmingham Vasculitis Activity Score were significantly lower in sub-Saharans and Afro-Caribbeans (P = 0.002 and P = 0.003, respectively). In contrast, in comparison with white Europeans, North Africans had only less frequent arthralgias (P = 0.004). Time to relapse was shorter for black sub-Saharans and Afro-Caribbeans compared with white Europeans [adjusted HR = 1.96 (95% CI: 1.09, 3.51) (P = 0.02)], and did not differ for North Africans. In contrast, overall survival was not significantly different according to ethnicity. Conclusion. Our findings indicated different GPA clinical presentations in white Europeans and sub-Saharans and Afro-Caribbeans, with black patients having more frequent severe granulomatous manifestations. In addition, time to relapse was significantly shorter for black sub-Saharans and Afro-Caribbeans compared with white Europeans.